Analisis Karakteristik Butir Soal Dengan Classical Test Teory Pada Pelajaran PKn di Sekolah Dasar - Irwan; Kamarudin; Bakri, Faldi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2024)
The research aims to determine the analysis of the characteristics of questions using Classical Test Theory in Civics Lessons in Elementary Schools. This research is quantitative research with descriptive methods. The subjects in this research were all fifth grade students at SD Negeri 1 Busoa, totaling 26 students and the objects in this research were the questions and answer keys for the Civics Class Odd Final Exam which consisted of 25 multiple choice questions made by the teacher. The data collection method uses the documentation method. Data analysis uses Validity, Reliability, Difference, Level of Difficulty, and Effectiveness of Distractors which are generated with computer assistance through the ANATES program. The results of this research show that: (1) in terms of validity, there are 9 valid items in the questions (36%) and 16 invalid items (64%). (2) in terms of reliability, the questions have low reliability with a reliability coefficient of 0.65. (3) in terms of Discriminating Power, the poor category is 2 items (8%), poor 6 items (24%), fair 7 items (28%), good 9 items (36%), and very good 1 item (4 %). (4) Judging from the level of difficulty, with difficult categories 5 items (20%), medium 9 items (36%), easy 11 items (44%). (5) Judging from the effectiveness of distractors, with categories very good 4 items (16%), good 3 items (12%), quite good 6 items (24%), poor 7 items (28%), and not good 5 items (20%).